Unforeseen effects: Hiccups unveiled by high-dose steroids in demyelination - Sai Niharika Tammineedi; Ramit Singla; Marilhia Cornejo Leon; Muskan Kohli; Chetan Saini; Aakanksha Pitiliya (eNeurologicalSci)
Background: Intractable hiccups, persisting beyond 48 h, pose a clinical challenge, particularly in demyelinating diseases like Neuromyelitis Optica (NMO) and Multiple Sclerosis (MS). Understanding the complex neural pathways of the hiccup reflex and the impact of high-dose steroid therapy is crucial for managing this rare but distressing symptom. The hiccup reflex involves afferents from the vagus, phrenic, and sympathetic nerves, with the reflex center in the anterior horns at the C3 to 5 level and the medulla oblongata. The potential interplay between demyelination and corticosteroid therapy in triggering persistent hiccups requires exploration. Case report: This case report details a 21-year-old male with undiagnosed demyelinating disorder, presenting persistent hiccups following high-dose steroid therapy for an acute disease flare. The patient's history included vertigo and progressive neurological symptoms, leading to an MS diagnosis with significant brain and spinal lesions. Persistent hiccups, initiated by steroid administration, were recurrent but responsive to metoclopramide after other measures failed. Discussion: The discussion centers on investigating the cause of hiccups in a patient with demyelination following steroid administration. Steroids' impact on neurological systems, including neurotransmitter function, and the potential disruption of neurological pathways due to demyelination may contribute to hiccups. Successful hiccup resolution with metoclopramide suggests a potential pharmacological approach for corticosteroid-induced hiccups in demyelinating diseases. This case emphasizes the need for further research into the intricate relationship between demyelination, steroid therapy, and hiccups to enhance management strategies for this uncommon yet impactful symptom.